Penatalaksanaan Pasien Diabetes Melitus Tipe 2 dengan Neuropati dan Retinopati Diabetikum Melalui Pendekatan Kedokteran Keluarga - Yuwandita Tamara Putri D; Azelia Nusadewiarti (CV. Jasa Sukses Abadi, 2020)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia. Currently DM has become a global health threat. 415 million people worldwide suffer from DM in 2015 and are expected to increase to 642 million by 2040. Application of family doctor based services based on evidence based medicine in patients by identifying risk factors, clinical problems, and patient management based on the framework of solving patient problems with approached and family approached patient. Analysis of this study is a case report. Primary data is obtained through history taking, physical examination and home visits to supplement family data, psychosocial and environmental data. Assessment is based on a holistic diagnosis from the beginning, the process, and the end of the study quantitatively and qualitatively. Patient ny. S 56 years old was diagnosed with Type 2 Diabetes Mellitus. Patients had internal risk aspects such as obesity, non-physical activity, offspring of diabetes mellitus, history of DM drug breakdown, curative treatment patterns. The external risk aspect of the patient is that the family does not understand the patient's disease and its complications, the family economy is low. Furthermore, the management consists of education about DM and its care for patients and families as well as initial GDS measurements. After evaluating, a decrease in GDS is obtained in patients.